2015 International Conference on Advanced Robotics (ICAR) 2015
DOI: 10.1109/icar.2015.7251433
|View full text |Cite
|
Sign up to set email alerts
|

System integration and preliminary in-vivo experiments of a robot for ultrasound guidance and monitoring during radiotherapy

Abstract: We are developing a cooperatively-controlled robot system in which a clinician and robot share control of a 3D ultrasound (US) probe. The goals of the system are to provide guidance for patient setup and real-time target monitoring during fractionated radiotherapy. Currently, there is limited use of realtime US image feedback during radiotherapy for lower abdominal organs and it has not yet been clinically applied for upper abdominal organs. One challenge is that placing an US probe on the patient produces tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…To address the first concern, the robot can be programmed to enable similar maneuverability to a free-hand approach with cooperative control, as described in our previous publications [36], [42]. With cooperative control, the robot and operator share control of the ultrasound probe via a force sensor that determines the direction of external forces applied (representative of the direction that the operator intends to move the probe).…”
Section: Discussionmentioning
confidence: 99%
“…To address the first concern, the robot can be programmed to enable similar maneuverability to a free-hand approach with cooperative control, as described in our previous publications [36], [42]. With cooperative control, the robot and operator share control of the ultrasound probe via a force sensor that determines the direction of external forces applied (representative of the direction that the operator intends to move the probe).…”
Section: Discussionmentioning
confidence: 99%
“…The robot software contains an interface to the optical tracking system (Polaris, Northern Digital Inc., Waterloo, ON, Canada). In our clinical environment, the interface to the ceiling-mounted tracking system is provided by a research version of the Clarity System, as described for the in vivo canine experiments reported in Sen et al (2015). For the phantom experiments reported here, we use a direct connection to a tracking system mounted on a tripod.…”
Section: Robot Systemmentioning
confidence: 99%
“…The workflow is separated into a planning day, where the planning images of the patient are acquired, and multiple (fractionated) treatment days, where the radiation therapy is delivered. A more detailed discussion of this workflow can be found in Bell et al (2014) and Sen et al (2015). In this section, we focus on the use of cooperative control within this workflow.…”
Section: Cooperative Control In the Radiotherapy Workflowmentioning
confidence: 99%
“…At this point, image based tracking methods can be used to track the needle tip. A robot can guide the US probe to collect images during operation [1]. The robot assisted US probe on the patient can produce tissue deformation, which might cause the imaging plane to shift, and could result in failure to track the needle tip.…”
Section: Introductionmentioning
confidence: 99%